2021
DOI: 10.15758/ajk.2021.23.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brief Dry Cupping on Muscle Soreness in the Gastrocnemius Muscle and Flexibility of the Ankle

Abstract: OBJECTIVES The purpose of this study was to analyze the effects of brief dry cupping on muscle soreness of the gastrocnemius muscle and range of motion (ROM) in the ankle.METHODS Thirty-six participants (age=29±10 yrs, ht=173.8±10.3 cm, wt=75.3±15.9 kg) were randomly assigned to three groups: A (no exercise), B (bilateral heel drops to exhaustion), and C (right unilateral heel drops to exhaustion). Dorsiflexion ROM was assessed bilaterally for all groups. All participants received the cupping protocol on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Their methodology included applying dry cupping to the gastrocnemius and assessing the effects on soreness and ROM using a 10-point VAS scale and repeated measures ANOVAs. The study found significant differences in muscle discomfort between the cupped and non-cupped calves, suggesting that dry cupping could reduce muscle soreness post-exercise, though its effect on ROM was not substantial (17). Wood et al ( 2021) explored the efficacy of dry cupping in patients with non-specific low back pain and chronic neck discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Their methodology included applying dry cupping to the gastrocnemius and assessing the effects on soreness and ROM using a 10-point VAS scale and repeated measures ANOVAs. The study found significant differences in muscle discomfort between the cupped and non-cupped calves, suggesting that dry cupping could reduce muscle soreness post-exercise, though its effect on ROM was not substantial (17). Wood et al ( 2021) explored the efficacy of dry cupping in patients with non-specific low back pain and chronic neck discomfort.…”
Section: Discussionmentioning
confidence: 99%